Measurement of cerebral and cerebellar volumes in children with fragile X syndrome - Kabakuş, Nimet; Aydin, Mustafa; Kavakli, Ahmet; Yildirim, Hanefi; Akin, Haluk (My University, 2006)
Background and Aim: Fragile X syndrome (FXS) is a genetic disease associated with mental retardation, speech and memory deficits, developmental/learning disabilities, and, frequently, also with neuropsychological findings. It is known that all these abnormal brain functions could be associated with morphological anomalies of various brain regions. We investigated possible brain volume variations in children with FXS who had significant neurobehavioral symptoms and cognitive deficits. Patients and Methods: This study was performed with 8 male FXS patients who were diagnosed cytogenetically. The Leiter International Performance Scales-Revised, the Stanford-Binet Intelligence Scale, the Vineland Social Maturity Scale, and DSM IV criteria were used for cognitive and behavioral assessment. The Cavalieri method, which is used to analyze the volumetric properties of smooth objects, was used for cranial volume measurements. Results: The mean age of the patients was 8.8 ± 4.4 years (range: 5-18 years). The mean IQ level was 59.8 ± 10.3 (range: 40-76). The vermis/total cerebellum ratios of the patients decreased with age (r = -0.851, P < 0.01). There was a correlation between this condition and neurobehavioral symptoms that increased with age. Conclusions: The study patients had decreased vermis/total cerebellum ratios, indicating the development of vermal atrophy with age. This vermal atrophy may have led to neurophysiological dysfunctions, cognitive deficits, and neurobehavioral phenotypes in the FXS patients. © TÜBİTAK.
Keywords: Brain volume; Cavalieri method; Fragile X syndrome; Magnetic resonance imaging; Mental retardation